The role of gut microbiome in mediating the effect of inflammatory bowel disease on hypertension: a two-step, two-sample Mendelian randomization study - Bao, Wei; Zhang, Yan; Huang, Xiao-Jia; Gu, Ning (Frontiers in Cardiovascular Medicine, 2024)
Objective: Investigating the causal connection that exists between inflammatory bowel disease (IBD) and hypertension(HT). To gain a deeper insight into the correlation among IBD, gut microbiota, and HT, we conducted a two-step, two-sample Mendelian randomization study.Methods: An investigation of genome-wide association study (GWAS) summary-level data was utilized to conduct a two-sample Mendelian randomization (MR) analysis of genetically predicted inflammatory bowel disease: (12,882cases, 21,770controls) on Systolic/Diastolic blood pressure (N = 2564). Subsequently, two-step MR analyses revealed that the relationship between IBD and SBP was partly mediated by Faecalicatena glycyrrhizinilyticum. The robustness of the findings was confirmed through several sensitivity assessments.Results: This MR study showed that increase in genetically predicted IBD was associated with higher risk of genetically predicted SBP(OR 1.08, 95% CI: 1.01-1.16, P < 0.05) and DBP(OR 1.09, 95% CI: 1.02-1.17, P < 0.05), respectively. Inverse variance weighted (IVW) MR analysis also showed that increase in genetically predicted IBD was associated with higher abundance Faecalicatena glycyrrhizinilyticum(OR 1.03, 95% CI: 1.01-1.04. P < 0.05), which subsequently associated with increased SBP risk(OR 1.42, 95% CI: 1.06-1.9, P < 0.05).Faecalicatena glycyrrhizinilyticum abundance in stool was responsible for mediating 11% of the genetically predicted IBD on SBP.The research proposed a causal link between Inflammatory Bowel Disease (IBD) and Hypertension (HT), with a little percentage of the impact being influenced by Faecalicatena glycyrrhizinilyticum in stool. Mitigating gut microbiome may decrease the heightened risk of hypertension in people with inflammatory bowel disease.